2004
DOI: 10.1115/1.1791641
|View full text |Cite
|
Sign up to set email alerts
|

Rotor-Stator Interactions in a Four-Stage Low-Speed Axial Compressor—Part I: Unsteady Profile Pressures and the Effect of Clocking

Abstract: This two-part paper presents detailed experimental investigations of unsteady aerodynamic blade row interactions in the four-stage Low-Speed Research Compressor of Dresden. In part I of the paper the unsteady profile pressure distributions for the nominal setup of the compressor are discussed. Furthermore, the effect of blade row clocking on the unsteady profile pressures is investigated. Part II deals with the unsteady aerodynamic blade forces, which are calculated from the measured profile pressure distribut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
12
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(12 citation statements)
references
References 24 publications
0
12
0
Order By: Relevance
“…Because the unsteady pressure fluctuation on the rotor blades changes nearly simultaneously along the whole blade chord [11,22], it can be assumed that the effect of the IGV wake and the potential effect appear nearly at the same point in time along the whole blade chord, respectively. Figures 9 and 10 show the unsteady pressure fluctuation on the PS and SS of the rotor blades along the chord length for the design point and the operating point near the stability limit at clocking position IGV 0.0 and IGV 0.6, respectively.…”
Section: Unsteady Pressure Fluctuations On the Rotor Bladesmentioning
confidence: 99%
See 1 more Smart Citation
“…Because the unsteady pressure fluctuation on the rotor blades changes nearly simultaneously along the whole blade chord [11,22], it can be assumed that the effect of the IGV wake and the potential effect appear nearly at the same point in time along the whole blade chord, respectively. Figures 9 and 10 show the unsteady pressure fluctuation on the PS and SS of the rotor blades along the chord length for the design point and the operating point near the stability limit at clocking position IGV 0.0 and IGV 0.6, respectively.…”
Section: Unsteady Pressure Fluctuations On the Rotor Bladesmentioning
confidence: 99%
“…Mailach and Vogeler [11] investigated the effect of stator clocking on unsteady pressure fluctuations on the rotor blades. In a 1.5-stage low-speed axial compressor, the effect of stator clocking on the unsteady pressure fluctuation and the blade pressure force of the rotor blades was numerically carried out by Jia and Vogeler [12].…”
Section: Introductionmentioning
confidence: 99%
“…Some authors [10,14] have identified changes in the rotor flowfield character due to vane clocking, but none have drawn conclusions connecting rotor performance differences with vane clocking with the efficiency changes. Results from Key [17] showed that the change in compressor efficiency associated with vane clocking is caused by losses on the downstream vane.…”
mentioning
confidence: 94%
“…Vane clocking also has a significant effect on the unsteady rotor blade loading [9,10]. The relative position of the upstream potential and vortical disturbances with respect to the downstream potential fields can have a strong effect on the rotor unsteady pressure amplitude.…”
mentioning
confidence: 98%
“…Mailach and Vogeler [12] performed experiments in a low-speed compressor with four identical stages. Blade surface pressures were measured on the suction surface and pressure surface at midspan on a single rotor in stage 3.…”
Section: Introductionmentioning
confidence: 99%